Polymorphisms of the NOS3 gene in Tunisian patients with Behçet's disease. (30th January 2015) - Kallel, A.; Sbaï, M. H.; Houman, M. H.; Sediri, Y.; Ouertani, D.; Smiti Khanfir, M.; Ben Ghorbel, I.; Jemaa, R.; Kaabachi, N.
Summary Behçet's disease (BD) is a multisystem inflammatory disease characterized by recurrent orogenital ulceration, ocular inflammation and skin lesions. Reduced plasma nitric oxide (NO) levels in patients with BD have been implicated in the development of the endothelial abnormalities and thrombotic complications occurring in these patients. Polymorphisms in the endothelial nitric oxide synthase gene (NOS3) have been inconsistently associated with BD. This inconsistency may derive from population stratification secondary to ethnic diversity, and consideration limited to only one rather than combinations of polymorphisms. We studied three genetic variations in the NOS3 gene: a single nucleotide polymorphism in the promoter region −786T>C, in exon 7 (Glu298Asp), and a variable number of tandem repeats in intron 4 (4a4b) of the NOS3 gene in 100 unrelated Tunisian patients with BD and 148 healthy controls. In addition, we also examined the association of NOS3 gene haplotypes with BD. Analyses of the Glu298Asp, −786T>C and 4a4b polymorphisms were made by the polymerase chain reaction (PCR) restriction fragment length polymorphism technique and PCR genotyping, respectively. The distribution of the Glu298Asp genotype differed significantly between patients with BD and controls (P = 0.01). Allele Asp298 was significantly more frequent in patients with BD than in controls (P = 0.005, OR = 1.70, 95% CI 1.14–2.54). In contrast, distribution of alleles and genotypes of −786T>C and 4a4b polymorphisms was not different between the control and BD group. However, the frequency of Asp‐T‐4b haplotype was significantly higher in patients with BD than in healthy controls. By gender, the signification remained only for heterozygous men (P = 0.03) and homozygous women (P = 0.02). These results suggest that Glu298Asp polymorphism of the NOS3 gene is associated with BD susceptibility in Tunisian patients.